Legacy [large type] - Roberts, Nora (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"Adrian Rizzo was seven when she met her father for the first time. That was the day he nearly killed her--before her mother, Lina, stepped in. Soon after, Adrian was dropped off at her grandparents' house. Lina, meanwhile, traveled the country promoting her fitness brand and turning it into a billion-dollar business. A decade later, Adrian has created her own line of yoga and workout videos. But while Lina dismisses the death threats that Adrian starts getting as a routine part of her daughter's growing celebrity, Adrian finds them unsettling. And sometimes it even seems like the terrifying messages are indeed routine. Until the murders start, and the escalation begins"--Page 4 of cover.